2021
DOI: 10.3390/ani11102983
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Liquid Feed for Pigs and Its Impact on the Porcine Gut Microbiome

Abstract: There is evidence that spontaneous fermentation frequently occurs in liquid pig feed that is intended to be delivered as fresh liquid feed, often with a resultant deterioration in the microbial and nutritional quality of the feed, which can negatively affect pig health and growth. Strategies including controlled fermentation with microbial inoculants, pre-fermentation or soaking of the cereal fraction of the diet, enzyme supplementation and dietary acidification have been employed to inhibit pathogens and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
(244 reference statements)
0
3
0
Order By: Relevance
“…Our meta-analysis revealed that ADG and ADFI were increased by 13.8% and 7.02% on average by Lactobacillus addition. It is suggested that Lactobacillus- based feeding could enhance feed palatability ( 54 ), which may explain the increased feed intake. A probiotic - improved G/F ratio was reported by us, suggesting that Lactobacillus supplementation brings about a more cost-effective feeding program than the control piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis revealed that ADG and ADFI were increased by 13.8% and 7.02% on average by Lactobacillus addition. It is suggested that Lactobacillus- based feeding could enhance feed palatability ( 54 ), which may explain the increased feed intake. A probiotic - improved G/F ratio was reported by us, suggesting that Lactobacillus supplementation brings about a more cost-effective feeding program than the control piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological studies of feed were conducted in the laboratory for the study of pig diseases of the National Research Center "Institute of Experimental and Clinical Veterinary Medicine" (Kharkiv) according to modern methods (Cullen et al, 2021). Identification and species affiliation of isolated field isolates of bacteria were performed by cultural-morphological and biochemical properties (Goodfellow et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Liquid feeds, which are fluid mixtures of water and feed mixed in specific proportions, offer numerous advantages over traditional solid dry feeds [1]. These advantages include an improved pigsty environment [2], reduced feed costs [3], the reduced use of antibiotics [4,5], the assisted weaning of piglets [6], improved palatability, and enhanced gut health [7,8]. As a result, liquid feeds offer the potential for a wide range of uses in pig farming.…”
Section: Introductionmentioning
confidence: 99%